DROGAS E ALUNOS USUÁRIOS DE DROGAS NA ESCOLA: ESTUDO DE REPRESENTAÇÕES SOCIAIS DE PROFESSORES DO ENSINO MÉDIO DA REDE ESTADUAL DE SÃO PAULO - Ribeiro, Fátima Regina Matos (2008)
This study presents a discussion about drugs and students who use them inside the school with a deep study of the social representation by teachers who working for the state teaching for the high school, in public schools in São Paulo. It brings back historical and social aspects that influenced the social representation about drugs in different contexts of the society, aiming to understand the way that they’re acting nowadays. It discusses the conceptual aspects of Social Representation Theory by Moscovici, considering the contributions from Jodelet e some other authors. The data collected through questionnaires and interviews were analyzed with the help of two softwares, the ALCESTE for lexical analysis and EVOC for analysis of association of words or phrases and also through a classical content analysis suggested by Maria Laura Puglisi Barbosa Franco. The result identified that social representations about drugs in school and the students that use drugs are anchored to the sensationalism and alarmist way that the mass media treats the subject influencing most of teachers that associate the drugs in schools with the violence. Also we could see that the objectivity of the student who uses drugs is notated as a disease and the researched group follows the social representations structured for a long time in the society, having normality as a synonym of health and the use of drugs as a diverting condition, resulting from the pathologies. So we hope to contribute for the reflection about the use of drugs in schools, an essential theme that needs to be faced to construct a way that leads to a fair and democratic education.(AU)